Consensus Statement on Use of Continuous Subcutaneous Insulin Infusion Therapy in the Hospital. (July 2018) - Thompson, Bithika; Korytkowski, Mary; Klonoff, David C.; Cook, Curtiss B.
In May 2017, the Diabetes Technology Society convened a panel of US experts on inpatient diabetes management to discuss the current and potential role of continuous subcutaneous insulin infusion (CSII) therapy in the hospital. The panel (1) discussed evidence for current use of CSII in the hospital, (2) recommended contraindications for use in the hospital, and (3) recommended guidelines to maximize chances for safe use of CSII in the hospital. Panel members agreed that larger, prospective, randomized studies are needed to evaluate safety and efficacy of CSII use in the hospital. As CSII technology becomes more complex and its use increases, it is imperative that institutional protocols be in place to ensure safe use of this technology and safe transitions across care areas. Providers need to be cognizant that not all patients currently using CSII as an outpatient are appropriate candidates for continued use in the hospital. This consensus statement provides guidelines for practitioners who may encounter patients using this technology in the inpatient setting.